Radio Network Selection for Tight-Coupled Wireless Networks - Alkhawlani, Mohammed M.; Alsalem, Kasim A. (IEEE, 2010)
In the tight-coupled next generation heterogeneous wireless networks, a user with a multi-interface terminal may have network access for different service providers using various technologies. Radio network selection (RNS) is the mechanism which decides how to select the most suitable access network (AN) based on the discovered accesses, QoS constraints, operator policies, user preferences and available system capacity and utilization. Optimizing the selection process is an important issue of research, which leads to reduction of network signalling and mobile device power loss and on the other hand improves network quality of service (QoS) and grade of service (GoS). This paper presents and designs a multi criteria RNS solution that considers an environment with a co-existed WWAN, WMAN, and WLAN. The developed solution contains two modules. The first module resides in the user terminal. It contains a network-assisted terminal-controlled algorithm to reflect the user viewpoint in the selection process. The second module resides in the common radio resource management (CRRM) entity. It contains a terminalassisted network-controlled algorithm to reflect the operator viewpoint of the selection decision. The developed solution uses a combined parallel fuzzy logic control and Multi-criteria decision making (MCDM) system to achieve scalable, flexible, general, and adaptable solution. The simulation results show that our solution has better and more robust performance over several reference algorithms.